KANTOR SEWA DAN CO-WORKING DENGAN PEMANFAATAN TAMAN ENERGI TERBARUKAN - Lidia Wiriani; Budi Adelar Sukada (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
As time goes by, currently the development growth in metropolitan cities has been leading to the ecosystem change, one of which is the decrease of the green open space (GOS). Nowdays Jakarta has only 9.8% green area and rather it is still far from 30% as a standard of green open space according to government’s Law No. 2 of 2007. In addition, another problem in Jakarta is the increase on the office electricity needs that generally due to the growth of office space demands in business and industrial, including start-up sectors that currently growing fastly. Development in cities is very often only focused on human interests on spaces and facilities, meanwhile on the other side, it just pay less attention to the surrounding environmenta impact. Therefore, this final project is promptly proposing a design and construction of a rental office and co-working office with the use of renewable energy park and solar energy with the aim of creating a more efficient electricity and also to provide a spacious green open spaces as charasteristic of an ecological building, to enable to promote a positive contribution to environmental improvement. The method approach used as reference in this project is the Leadership in Energy and Environmental Design (LEED) standard. This project will not only offer office facilities but also a multifunctional facilities such as coffee shop, mini market, food court, book and stationery store, fitness center, fun games area, jogging track, basketball court, and ATM corner, while for green open space (GOS) there is also renewable energy park, namely bioo panel garden, irrigation ponds, and tree areas. Keywords: Green office space (GOS); electricity consumption; rental and co-working office; renewable energy parkAbstrakSeiring berjalannya waktu, saat ini maraknya pembangunan di kota metropolitan telah berdampak pada perubahan ekosistem, salah satunya yaitu isu lingkungan seperti keterbatasan ruang terbuka hijau (RTH). Saat ini Jakarta memiliki kawasan hijau hanya sekitar 9,8% yang masih jauh dari 30% sebagai standar ruang terbuka hijau di kota berdasarkan Undang-Undang No. 2 Tahun 2007. Selain itu, masalah lainnya di Jakarta adalah meningkatnya pemakaian listrik perkantoran yang umumnya dikarenakan adanya peningkatan kebutuhan ruang usaha di dunia bisnis dan industri kreatif (start-up) yang sedang berkembang pesat. Pembangunan di kota seringkali hanya berpusat pada kebutuhan manusia akan ruang dan fasilitasnya, sementara disisi lain kurang memperhatikan dampaknya terhadap lingkungan sekitar. Adapun proyek pada tugas akhir ini adalah untuk mengajukan suatu rancangan pembangunan kantor sewa dan co-working dengan pemanfaatan taman energi terbarukan agar tercipta kelistrikan yang lebih efisien, serta perwujudan ruang terbuka hijau yang luas sebagai ciri bangunan ekologis, sehingga diharapkan dapat memberikan kontribusi untuk perbaikan lingkungan. Paradigma utama dalam mendesain proyek ini adalah bagaimana menciptakan enviromental balance dengan pendekatan ecosystem environment dan energy efficiency. Adapun pendekatan metode yang digunakan sebagai acuan adalah standar Leadership in Energy and Environmental Design (LEED). Proyek ini disamping menyediakan sarana perkantoran, juga menawarkan fasilitas yang multifungsi seperti coffeeshop, minimarket, food court, toko buku dan alat tulis, fitness center, fun games area, jogging track, lapangan basket, serta gerai ATM. Sementara untuk area ruang terbuka hijau (RTH) tersedia taman energi terbarukan (renewable energy park) yaitu bioo panel garden, kolam irigasi, dan area taman pohon.